A foamed nickel self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material and its preparation method and application

By growing MOF structures on the foam nickel skeleton, Co3S4/Ni3S2/NF heterojunction electrocatalytic composites were prepared, which solved the instability of sulfide OER electrocatalytic composites under alkaline conditions, and realized the electrolytic water production High-efficiency and stable catalytic performance in the hydrogen process.

CN118904360BActive Publication Date: 2025-01-10INNER MONGOLIA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411407749.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing sulfide OER electrocatalytic composites have thermodynamic instability under alkaline conditions, resulting in insufficient catalytic activity and stability, making it difficult to work efficiently in the process of electrolyzing hydrogen production.

Method used

Using foam nickel self-supported cobalt nickel bimetallic sulfide heterojunction electrocatalytic composite material, the Co3S4/Ni3S2/NF heterojunction electrocatalytic composite material is prepared by hydrothermal method by hydrothermal method. Its electronic structure and active sites improve catalytic performance and stability.

Benefits of technology

It has achieved excellent catalytic performance and stability in electrocatalytic anode oxygen evolution reaction and urea oxidation reaction, significantly improving the active area and charge transfer rate of the electrocatalytic composite material, and extending the service life of the electrocatalytic composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118904360B_ABST
    Figure CN118904360B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrocatalysis technology, and discloses a nickel foam self-supporting cobalt nickel bimetallic sulfide heterojunction electrocatalytic composite material and its preparation method and application. The preparation method comprises: dissolving a cobalt salt and 2-methylimidazole in water to obtain a mixed solution; immersing a nickel foam substrate in the mixed solution to obtain a zeolite imidazole ester framework material with nickel foam as a carrier, calcining in an inert atmosphere to obtain a metal organic framework material, adding a thiourea solution for hydrothermal reaction, and obtaining a nickel foam self-supporting cobalt nickel bimetallic sulfide heterojunction electrocatalytic composite material Co3S4 / Ni3S2 / NF, wherein the electrocatalytic composite material has a stable three-dimensional cross-intersecting nanosheet structure, avoids the problems of the composite material falling off and dissolving during the reaction, significantly improves the stability, has a synergistic effect between the heterogeneous interfaces, and a large specific surface area and abundant vacancies are conducive to exposing active sites, thereby simultaneously showing excellent electrocatalytic performance and high stability in UOR and OER.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, and a preparation method and application thereof. Background Art

[0002] Hydrogen, as a highly potential green new energy, is an ideal choice to replace traditional fossil fuels. Among them, the electrolysis of water to produce hydrogen using renewable and sustainable energy has attracted more and more attention due to its zero carbon and zero pollution emissions. Water electrolysis is an attractive and promising energy conversion method. However, due to the high energy barriers of the cathode and anode reactions, especially the slow kinetics of the anodic oxygen evolution reaction (OER) process itself, the large-scale electricity consumption of hydrogen production leads to the dilemma of low conversion efficiency. At present, the widely used commercial OER electrocatalytic composite materials are known precious metals (such as Ru and Ir), but due to the high price and scarce reserves. Finding and developing low-cost and energy-efficient electrocatalytic composite materials has become a common goal in the current research field. A variety of transition metal carbides, sulfides, phosphides and selenides have shown high efficiency and persistent activity in the cathode hydrogen evolution reaction (HER) or OER process. In addition, urea has gradually come into people's view as a complete water splitting anodic oxidation reaction instead of oxygen evolution reaction. A key application of the urea oxidation reaction (UOR) is as an anode reaction in urea fuel cells, where urea replaces hydrogen as a fuel to promote the conversion of chemical energy into electrical energy, providing a promising path to advance energy conversion technology and create a new era of sustainable power generation. Studies have shown that the construction of heterogeneous interfaces facilitates the transfer of charge in electrocatalytic composites, while optimizing the electronic structure of different phases, further regulating the adsorption and desorption capacity of electrocatalytic composites for free radicals, and promoting the kinetic process of water electrolysis in the positive direction. Sulfide OER electrocatalytic composites have good OER activity and good appearance stability, and are one of the most important branches of low-valent metal OER electrocatalytic composites. Despite great efforts in the development of new sulfide OER electrocatalytic composites, sulfides have the problem of thermodynamic instability under alkaline OER conditions. Studies have shown that sulfide OER electrocatalytic composites undergo structural reconstruction during the OER process, and it is unanimously believed that sulfides are a "pre-electrocatalytic composite". However, the stability of transition metal sulfides (TMSs) is generally poor at this stage. The reason may be that in the alkaline OER process, sulfides are more likely to undergo surface reconstruction than other compounds, and the new phases generated by reconstruction are mostly hydroxides and oxyhydroxyls. Therefore, it is necessary to develop a sulfide electrocatalyst material that can simultaneously improve catalytic activity and stability.

[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing and applying a nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, so as to solve the problem of how to prepare a metal sulfide electrocatalytic material that has excellent catalytic performance and stability in both the electrocatalytic anode oxygen evolution reaction and the urea oxidation reaction.

[0005] The technical solution of the present invention is as follows:

[0006] The first aspect of the present invention provides a method for preparing a nickel foam (NF) self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, comprising the steps of:

[0007] S1, dissolving cobalt salt and 2-methylimidazole in water, mixing and stirring to obtain a mixed solution;

[0008] S2, ultrasonically cleaning the nickel foam substrate, and immersing the cleaned nickel foam substrate in the mixed solution to react, thereby obtaining a zeolite imidazolate framework material with nickel foam as a carrier, which is recorded as ZIF-67 / NF;

[0009] S3, calcining the ZIF-67 / NF in an inert atmosphere to obtain a metal organic framework material;

[0010] S4. Add the metal organic framework material into a thiourea solution and perform a hydrothermal reaction to obtain the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, recorded as Co3S4 / Ni3S2 / NF.

[0011] In step S1, optionally, the cobalt salt is one of cobalt nitrate, cobalt sulfate and cobalt chloride.

[0012] In step S1, optionally, the molar ratio of the cobalt salt to 2-methylimidazole is 1:4.9 to 1:5.1.

[0013] In step S2, optionally, the concentration of the hydrochloric acid solution is 2.5-3.5 mol / L.

[0014] Optionally, the ultrasonic cleaning time is 20 to 30 minutes.

[0015] In step S2, optionally, the conditions for immersing the cleaned nickel foam substrate in the mixed solution for reaction are: reaction temperature is 25-35°C, and reaction time is 11.5-12.5h.

[0016] In step S3, optionally, the calcination temperature is 590-610° C., and the calcination time is 1.45-1.55 h.

[0017] Optionally, the heating rate of the calcination is 0.98-1.02°C / min.

[0018] In step S4, optionally, the concentration of the thiourea solution is 0.3-0.35 mol / L.

[0019] Optionally, the temperature of the hydrothermal reaction is 155-165° C., and the time of the hydrothermal reaction is 8-8.5 h.

[0020] The second aspect of the present invention provides a nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, which is prepared by the preparation method of the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material.

[0021] The third aspect of the present invention provides an application of the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material in electrocatalytic anode oxygen evolution reaction (OER) and urea oxidation reaction (UOR).

[0022] Beneficial effects:

[0023] The present invention prepares the Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material by synthesizing a nano-sheet MOF loaded on a NF substrate, calcining and carbonizing the MOF in a N2 atmosphere, and then performing sulfurization by a hydrothermal method.

[0024] The heterogeneous interfaces of the Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material produce a synergistic effect, which accelerates the electron transfer rate, changes the charge distribution, and is beneficial to improving the OER catalytic activity.

[0025] The Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material has a rich vacancy structure, which is conducive to exposing more active sites and provides convenient conditions for the redistribution of charges and the improvement of the activity of the electrocatalytic composite material.

[0026] In the OER and UOR reactions, the surface of the Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material is reconstructed to form metal hydroxide active substances. After reconstruction, the sulfur atom vacancies are partially transformed into oxygen atom vacancies. The transformation of the vacancy structure exposes more low-coordinated species, redistributes the surface charge, and improves the performance of the electrocatalytic composite material. The reconstruction of Ni in the electrocatalytic composite material can promote the catalytic reaction, and the sulfide of Co has a relatively stable spinel structure.

[0027] Therefore, the present invention increases the active area of ​​the electrocatalytic composite material and increases the active sites by growing a stable three-dimensional cross-shaped nanosheet ZIF-67 MOF structure on a nickel foam skeleton. The obtained Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material exhibits excellent electrochemical catalytic performance in both OER and UOR, as well as the stability of the morphology and catalytic performance during the catalytic process. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the synthesis of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in an embodiment of the present invention.

[0029] Figure 2 This is the XRD spectrum of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in an embodiment of the present invention.

[0030] Figure 3 a is the SEM image of ZIF-67 in Example 1 of the present invention; b is the SEM image of the electrocatalytic composite material Co3S4 / Ni3S2 / NF, c is the high-resolution TEM image, d is the SAED image, e is the HAADF-STEM image (with the energy dispersion spectrum embedded in it), and fj are the element distribution maps of Co, Ni, S, and N, respectively.

[0031] Figure 4 XPS spectra of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in the embodiment of the present invention and the composite materials Co3S4 / NF and Ni3S2 / NF in the comparative example: a is the full XPS spectrum, b is the Co 2p spectrum, c is the Ni 2p spectrum, and d is the S 2p spectrum.

[0032] Figure 5 This is an electron paramagnetic resonance (EPR) spectrum of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in an embodiment of the present invention.

[0033] Figure 6 The OER performance test results of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in 1.0M KOH electrolyte at room temperature in the embodiment of the present invention are: aLSV polarization curve, boverpotential comparison at different current densities, cTafel slope, dElectrochemical impedance spectroscopy test.

[0034] Figure 7 The potential range of 0 V to 0.1 V (vs. Hg / HgO) for different electrocatalytic composites is 30 mV·s -1 Up to 80mV·s -1 CV curves at different scan rates: a is RuO2 / NF, b is Co3S4 / NF, c is Ni3S2 / NF, and d is Co3S4 / Ni3S2 / NF.

[0035] Figure 8 The OER performance test of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in the embodiment of the present invention is shown as follows: a is the double layer capacitance, b is the Faraday efficiency of the OER process, and c is the current density of 10 mA cm - 2 a is the chronoamperometric curve of the electrocatalytic composite material Co3S4 / Ni3S2 / NF, and d is the comparison of the properties of different electrocatalytic composite materials.

[0036] Fig. 9 The UOR performance test of the electrocatalytic composite material Co3S4 / Ni3S2 / NF in the embodiment of the present invention is shown in FIG. 1 : a is the LSV polarization curve, b is the Tafel slope, c is the electrochemical impedance spectroscopy test, and d is the double layer capacitance. DETAILED DESCRIPTION

[0037] The present invention provides a foamed nickel self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material and a preparation method and application thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0039] The embodiment of the present invention provides a method for preparing a nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, comprising the following steps:

[0040] S1, dissolving cobalt salt and 2-methylimidazole in water, mixing and stirring to obtain a mixed solution;

[0041] S2, ultrasonically cleaning the nickel foam substrate, and immersing the cleaned nickel foam substrate in the mixed solution to react, thereby obtaining a zeolite imidazolate framework material with nickel foam as a carrier, which is recorded as ZIF-67 / NF;

[0042] S3, calcining the ZIF-67 / NF in an inert atmosphere to obtain a metal organic framework material;

[0043] S4. Add the metal organic framework material into a thiourea solution and perform a hydrothermal reaction to obtain the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, recorded as Co3S4 / Ni3S2 / NF.

[0044] In step S1, in some embodiments, the cobalt salt is one of cobalt nitrate, cobalt sulfate and cobalt chloride.

[0045] In some embodiments, the molar ratio of the cobalt salt to 2-methylimidazole is 1:4.9 to 1:5.1.

[0046] In a preferred embodiment, the molar ratio of the cobalt salt to 2-methylimidazole is 1:5.

[0047] In step S2, in some embodiments, the concentration of the hydrochloric acid solution is 2.5-3.5 mol / L.

[0048] In a preferred embodiment, the concentration of the hydrochloric acid solution is 3 mol / L.

[0049] In some embodiments, the ultrasonic cleaning time is 20 to 30 minutes.

[0050] In step S2, in some embodiments, the conditions for immersing the cleaned nickel foam substrate in the mixed solution for reaction are: reaction temperature is 25-35° C., and reaction time is 11.5-12.5 h.

[0051] In a preferred embodiment, the conditions for immersing the cleaned nickel foam substrate in the mixed solution for reaction are: reaction temperature is 25° C., and reaction time is 12 h.

[0052] In step S3, in some embodiments, the calcination temperature is 590-610° C., and the calcination time is 1.45-1.55 h.

[0053] In a preferred embodiment, the calcination temperature is 600° C. and the calcination time is 1.5 h.

[0054] In some embodiments, the heating rate of the calcination is 0.98-1.02° C. / min.

[0055] In a preferred embodiment, the heating rate of the calcination is 1°C / min.

[0056] In step S4, in some embodiments, the concentration of the thiourea solution is 0.3-0.35 mol / L.

[0057] In some embodiments, the temperature of the hydrothermal reaction is 155-165° C., and the time of the hydrothermal reaction is 8-8.5 h.

[0058] In a preferred embodiment, the temperature of the hydrothermal reaction is 160° C., and the time of the hydrothermal reaction is 8 hours.

[0059] The embodiment of the present invention provides a nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, which is prepared by the preparation method of the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material.

[0060] The embodiment of the present invention provides an application of the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material in electrocatalytic anode oxygen evolution reaction and urea oxidation reaction.

[0061] The following describes it in detail through specific embodiments.

[0062] Example 1

[0063] The synthesis process of this embodiment is as follows Figure 1 As shown, the specific steps are as follows:

[0064] Nickel foam (NF) substrate pretreatment

[0065] Pretreatment of nickel foam substrate: A 2 cm × 3 cm × 1.5 mm NF sheet was ultrasonicated in 3M hydrochloric acid solution for 30 min, in anhydrous ethanol for 20 min, and in deionized water for 20 min, then washed three times with deionized water, and finally dried in a vacuum oven at 60 °C for 3 h to obtain a clean NF.

[0066] Synthesis of ZIF-67 / NF

[0067] Disperse 1 mmol of cobalt nitrate hexahydrate and 5 mmol of 2-methylimidazole in 40 ml of deionized water and stir at room temperature for 0.5 h until dissolved. Then take a piece of 2*3 cm 2 The treated NF and the above liquid were quickly transferred to a 100 mL beaker and reacted and soaked at room temperature for 12 hours to obtain a product labeled as ZIF-67 / NF. After the reaction, the above product was taken out, rinsed with deionized water and ethanol several times, and dried in an oven at 70°C.

[0068] Synthesis of Co3S4 / Ni3S2 / NF

[0069] ZIF-67 / NF was placed in a porcelain boat and then transferred to a tube furnace. -1The temperature was raised to 600°C at a heating rate and kept for 1.5h. After cooling naturally, the intermediate product retaining the MOF skeleton was taken out. 0.5mg of thiourea was dispersed in 20mL of deionized water and stirred at room temperature for 0.5h until dissolved. The solution and the intermediate product were then transferred to a 20mL polytetrafluoroethylene reactor and reacted at 160°C in a constant temperature oven for 8h. After the reaction was completed, it was naturally cooled to room temperature, and the above product was rinsed three times with deionized water and anhydrous ethanol, and dried at 70°C for 5h to obtain a product example, marked as Co3S4 / Ni3S2 / NF.

[0070] Comparative Example 1

[0071] Synthesis of Co3S4 / NF

[0072] Disperse 1 mmol of cobalt nitrate hexahydrate and 5 mmol of 2-methylimidazole in 40 ml of deionized water, stir at room temperature for 0.5 h until dissolved, and soak at room temperature for 12 h. After the reaction, take out the above product, centrifuge the powder, rinse it with deionized water and ethanol several times, and then dry it in an oven at 70 ° C to obtain ZIF-67 powder. Then, place ZIF-67 in a porcelain boat, and then transfer it to a tube furnace. In a nitrogen atmosphere, heat it at 1 ° C min -1 The temperature was raised to 600 °C at a heating rate and kept at this temperature for 1.5 h. After cooling naturally, the intermediate product retaining the MOF skeleton was obtained. 0.5 mg of thiourea and ZIF-67 powder were dispersed in 20 mL of deionized water and stirred at room temperature for 0.5 h until dissolved. The solution and the intermediate product were then transferred to a 20 mL polytetrafluoroethylene reactor and reacted at 160 °C in a constant temperature oven for 8 h. After the reaction, the powder was separated by centrifugation, rinsed several times with alcohol and deionized water, and then dried in an oven at 70 °C to obtain Co3S4 powder. The Co3S4 powder was configured to 1 mg μL -1 The prepared solution was coated on the treated NF with a loading of 80 mg cm -2 , and obtained product comparison sample 1, recorded as Co3S4 / NF.

[0073] Comparative Example 2

[0074] Synthesis of Ni3S2 / NF

[0075] 0.5 g of thiourea was dispersed in 20 mL of deionized water and stirred at room temperature for 0.5 h until dissolved to obtain a solution. The treated NF and solution were then transferred to a 20 mL polytetrafluoroethylene reactor and reacted at 160 ° C in a constant temperature oven for 8 h. After the reaction was completed, it was naturally cooled to room temperature. The above product was rinsed with deionized water and anhydrous ethanol three times each, and then dried at 70 ° C for 5 h to obtain product comparison sample 2, which was recorded as Ni3S2 / NF.

[0076] Characterization and testing

[0077] Electrochemical testing

[0078] The performance results of electrocatalytic composite materials were obtained using the Chenhua CHI760E electrochemical workstation and three-electrode test system. The three-electrode system consists of an electrode clip (working electrode), a mercury / mercury oxide electrode (reference electrode), a carbon rod (counter electrode) and an electrolyte. The potential conversion formula between the mercury / mercury oxide electrode and the reversible hydrogen electrode (RHE) is: E RHE =E Hg / HgO +0.059pH+0.098.

[0079] (1) Oxygen evolution reaction (OER) performance test

[0080] Install a three-electrode test system, and the electrolyte is 1M KOH. Cut the example sample (Co3S4 / Ni3S2 / NF), comparative sample 1 (Co3S4 / NF), and comparative sample 2 (Ni3S2 / NF) into 0.5cm*1.5cm samples, fix the cut samples with electrode clamps, and ensure that the area of ​​the sample immersed in the liquid surface is 0.5cm*0.5cm, and then start the test. Use cyclic voltammetry (CV) to activate the electrocatalytic composite material, with a scan rate of 100mV·s -1 The linear sweep voltammetry (LSV) curve was then tested until the curves basically overlapped. To avoid the overlap of the oxidation peak and the OER signal peak due to the positive scan, the voltage was set at 5 mV·s -1 The LSV curve was obtained by reverse scanning in the potential range of 1-0V. The double-layer capacitance (Cdl) was tested at different scanning rates in the non-Faraday region (0V-0.1V vs. Hg / HgO) to obtain the CV curve. The scanning rate was used as the horizontal axis, and the middle value of the point interval was taken as the vertical axis after the difference was divided by two. The slope obtained after fitting was the double-layer capacitance. The stability data of the electrocatalytic composite material was controlled by the chronoamperometry with the current density (10mA cm -2 , 100mA cm -2 ) tested.

[0081] (2) Urea oxidation reaction (UOR) performance test

[0082] Install a three-electrode test system, the electrolyte is 1.0M KOH / 0.5M urea. Cut the example sample (Co3S4 / Ni3S2 / NF), comparative sample 1 (Co3S4 / NF), and comparative sample 2 (Ni3S2 / NF) into 0.5cm*1.5cm samples, fix the cut samples with electrode clamps, ensure that the area of ​​the sample immersed in the liquid surface is 0.5cm*0.5cm, and then start the test. The test method is the same as the OER performance test.

[0083] X-ray diffraction (XRD) characterization

[0084] The phase of Co3S4 / Ni3S2 / NF electrocatalytic composite material was characterized by XRD. Figure 2 As shown, the three diffraction peaks (green lines) at 44.5°, 51.8°, and 76.4° correspond to the NF substrate (JCPDS No. 04-0850)'s (111), (200) and (220) planes; the six diffraction peaks (blue lines) at 22.4°, 31.6°, 38.3°, 50.3°, 55.8° and 73.4° correspond to the (101), (110), (021), (211), (300) and (214) planes of Ni3S2 (PDF#44-1418), respectively; the five diffraction peaks (purple lines) at 31.8°, 38.7°, 50.6°, 55.2° and 78.3° correspond to the (311), (400), (511), (440) and (731) planes of Co3S4 (PDF#24-0334), respectively. This surface successfully synthesized the Co3S4 / Ni3S2 heterojunction electrocatalytic composite material loaded on the NF substrate, denoted as Co3S4 / Ni3S2 / NF.

[0085] Scanning electron microscopy (SEM) characterization

[0086] From the SEM images, it can be observed that Figure 3 As shown in a, the precursor MOF is a nanosheet structure. After carbonization and hydrothermal sulfurization in a nitrogen atmosphere, the MOF skeleton can still be kept intact. The morphology is still a three-dimensional cross-shaped nano-leaf structure. There are small particle protrusions on the surface of the leaf, which increases the active area of ​​the electrocatalytic composite material and increases the active sites. The scanning electron microscope image of the Co3S4 / Ni3S2 / NF electrocatalytic composite material is shown in Figure 3 As shown in (b), the morphology of the nanosheets did not change after treatment, but the surface roughness increased and was covered with nanoparticle structures. The structure was further analyzed by high-resolution transmission electron microscopy (HR-TEM) and selected area electron diffraction (SAED), as shown in Figure 2. Figure 3 As shown in c, the (110) and (202) crystal planes of Ni3S2 can be clearly observed, with lattice fringe spacing of 0.29nm and 0.20nm, respectively. On the left, the (620) and (511) crystal planes of Co3S4 are observed, with lattice fringe spacing of 0.15nm and 0.18nm, respectively. This test result proves that the electrocatalytic composite material is composed of two phases, Co3S4 and Ni3S2, and Ni3S2 is wrapped on the surface of Co3S4. This conclusion can be further verified by the selected area electron diffraction pattern of the corresponding area, as shown in Figure 3As shown in (d), the electron diffraction in this area corresponds to the (620), (511) and (400) crystal planes of Co3S4, and the (110) and (202) crystal planes of Ni3S2 are also clearly visible.

[0087] The above test results show that the Co3S4 / Ni3S2 / NF electrocatalytic composite material was successfully synthesized in the embodiment of the present invention. The high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) image of the electrocatalytic composite material ( Figure 3 e) and the elemental surface scan map show that Co, Ni, S and N elements are evenly distributed ( Figure 3 f~j in ). Figure 3 The energy dispersion spectrum embedded in the e in the graph shows that the contents of C, N and Co are relatively high, and combined with SEM analysis, it can be proved that the MOF skeleton is relatively intact. The content of Ni is relatively low, but its electronegativity is stronger than that of Co, which can accelerate the electron transfer rate between heterogeneous structures and change the charge distribution structure on the surface of the electrocatalytic composite material.

[0088] To further study the electronic structure of the electrocatalytic composite Co3S4 / Ni3S2 / NF, the surface element composition of the electrocatalytic composite was systematically characterized by X-ray photoelectron spectroscopy (XPS). Figure 4 shown.

[0089] The XPS spectrum shows the presence of Ni, Co, N, C, and S elements, among which the N 1s and C 1s signals are attributed to the MOF framework of the electrocatalytic composite ( Figure 4 As shown in a in Figure 4 As shown in (b), the peaks near 796.3 eV and 781.2 eV correspond to the Co 2p 1 / 2 and Co 2p 3 / 2 Among them, the binding energy is 793.6eV (2p 1 / 2 ) and 778.2eV (2p 3 / 2 ) corresponds to the two characteristic peaks of Co 3+ Compared with single sulfide, Co 2+ With Co 3+ The peak area ratio increased significantly, which resulted in some Co 3+ Reduced to Co 2+ , the electrocatalytic composite material may generate sulfur vacancies during the sulfurization process, generating Co species with low coordination number. Figure 4 As shown in Figure (c), for the Ni 2p spectrum of Co3S4 / Ni3S2 / NF, the characteristic peaks at 855.4 eV and 872.7 eV binding energy correspond to the typical Ni 2+ 2p 3 / 2 and 2p1 / 2 Compared with Ni3S2 / NF sample, Ni 2+ The peak shows a significant negative shift, which indicates that there is a strong electronic interaction at the Co3S4 / Ni3S2 / NF interface. The S 2p spectrum shows that the SM bond peak area of ​​the heterostructure is significantly increased compared with the control sample. At the same time, the S 2- The characteristic peaks are attributed to sulfur vacancies, which can also be confirmed in EPR (such as Figure 5 Compared with the S 2p spectrum of Ni3S2 / NF, its 2p 3 / 2 and 2p 1 / 2 The characteristic peak binding energy shows a positive shift of 0.2 eV (such as Figure 4 The above characteristic peaks move in different degrees, which can confirm that there is a strong electronic interaction between the Co3S4 phase and the Ni3S2 phase, which regulates the binding energy of the metal-S bond. The sulfur vacancy indicates that the metal-S bond is broken and coordination loss occurs, which will cause electrons to redistribute and transfer on the heterogeneous interface and promote the catalytic kinetic process. The fitting of the binding energy at 162.8eV and 164.1eV corresponds to 2p 3 / 2 and 2p 1 / 2 , both characteristic peaks are attributed to the SM bonds.

[0090] Electrocatalytic performance test

[0091] Based on a typical three-electrode system, the OER electrocatalytic activities of the electrocatalytic composites Co3S4 / Ni3S2 / NF, Ni3S2 / NF and Co3S4 / NF as well as those compared with the commercial electrocatalytic composite RuO2 / NF were systematically evaluated in 1.0 M KOH electrolyte.

[0092] like Figure 6 a in the figure is the LSV curve of the electrocatalytic composite material after iR correction. The electrocatalytic composite material Co3S4 / Ni3S2 / NF exhibits excellent catalytic activity at current densities of 10, 50 and 100 mA cm -2 When the overpotential is as low as 200, 277 and 319 mV, respectively, which is much lower than the overpotential of Ni3S2 / NF (η10 = 230 mV, η50 = 339 mV) and Co3S4 / NF (η10 = 304 mV, η50 = 422 mV). The performance of the electrocatalytic composite Co3S4 / Ni3S2 / NF is also better than that of the commercial electrocatalytic composite RuO2 / NF (η10 = 300 mV, η50 = 430 mV, η100 = 500 mV) (such as Figure 6Meanwhile, the Tafel slope of the electrocatalytic composite Co3S4 / Ni3S2 / NF is 57.4 mV dec -1 ( Figure 6 c) is lower than Ni3S2 / NF (116.2mV dec -1 )、Co3S4 / NF(136.4mV dec -1 ) and RuO2 / NF (140.2mV dec -1 ), which indicates that the electrocatalytic composite material Co3S4 / Ni3S2 / NF has excellent catalytic kinetics. The charge transfer rate (Rct) of the electrocatalytic composite material was further studied by electrochemical impedance spectroscopy (EIS). The impedance value is negatively correlated with the electron transfer rate. The larger the impedance value, the slower the electron transfer rate of the electrocatalytic composite material. Figure 6 As can be seen from d in the figure, the Rct of the electrocatalytic composite material Co3S4 / Ni3S2 / NF is smaller than that of other electrocatalytic composite materials such as Ni3S2 / NF, Co3S4 / NF and RuO2 / NF, indicating that the electrocatalytic composite material Co3S4 / Ni3S2 / NF has the fastest electron transfer rate during the OER catalysis process.

[0093] In order to further explore the electrochemical activity of different electrocatalytic composites, the double-layer capacitance of the electrocatalytic composites was tested at different scan rates in the non-Faraday potential region, and then the Cdl value of the sample was fitted by cyclic voltammetry curves to evaluate the electrochemically active surface area (ECSA) of the electrocatalytic composites. Figure 7 As shown in a~d in Figure 1, the Cdl value of the electrocatalytic composite material Co3S4 / Ni3S2 / NF is as high as 26.9mF cm -2 , significantly better than Ni3S2 / NF (9.2mF cm -2 )、Co3S4 / NF(5.3mFcm -2 ) and RuO2 / NF (5.9 mF cm -2 ).

[0094] Depend on Figure 8 The a in the figure shows that Co3S4 / Ni3S2 / NF has the largest electrochemical active area and the largest number of exposed active sites.

[0095] exist Figure 8 In figure b, the Faradaic efficiency of the Co3S4 / Ni3S2 / NF electrocatalytic composite material in the OER process was calculated to be 98.39%.

[0096] The stability of the sample is tested by measuring the it curve, such as Figure 8 As shown in c, at 10 mA cm -2Under a constant current density of , the electrocatalytic composite material Co3S4 / Ni3S2 / NF can remain stable for more than 100 hours with a loss of only 5%, indicating that Co3S4 / Ni3S2 / NF has good electrochemical stability and is significantly improved compared with the stability of other nickel-based sulfides.

[0097] like Figure 8 As shown in (d), the electrocatalytic composite Co3S4 / Ni3S2 / NF exhibits excellent OER catalytic activity compared with other transition metal-based electrocatalytic composites.

[0098] Considering that the Ni element of the Co3S4 / Ni3S2 / NF electrocatalytic composite material can serve as an active site for the urea electrooxidation reaction after the OER reaction, the UOR reaction performance of Co3S4 / Ni3S2 / NF, Ni3S2 / NF and Co3S4 / NF composite materials was studied in 1.0M KOH / 0.5M urea electrolyte using a classic three-electrode system. Fig. 9 As shown in a, it can be found that under alkaline conditions (1.0 M KOH / 0.5 M urea), the electrocatalytic composite material Co3S4 / Ni3S2 / NF has the best UOR catalytic activity at 100 mA cm -2 At a current density of 1.5 volts, the voltage of Co3S4 / Ni3S2 / NF is 1.36 V, which is significantly better than Ni3S2 / NF and Co3S4 / NF. The reaction kinetics of the electrocatalytic composite material was evaluated by the Tafel slope. Fig. 9 As can be seen in b, the electrocatalytic composite material Co3S4 / Ni3S2 / NF has the smallest Tafel slope (22.3 mV dec -1 ), compared with Ni3S2 / NF (34.5mV dec -1 ) and Co3S4 / NF (65.7mVdec -1 ), indicating that the Co3S4 / Ni3S2 / NF electrocatalytic composite material has the fastest reaction kinetics. Fig. 9 From the c in the figure, we can see that the electrocatalytic composite material Co3S4 / Ni3S2 / NF has a relatively low charge transfer resistance (Rct), which is lower than that of Ni3S2 / NF and Co3S4 / NF. This indicates that the interfacial charge transfer resistance of Co3S4 / Ni3S2 / NF is minimal, and also indicates that Co3S4 / Ni3S2 / NF improves the reaction kinetics of the UOR reaction. At the same time, the double layer capacitance ( Fig. 9 The Cdl value of the electrocatalytic composite material Co3S4 / Ni3S2 / NF is as high as 19.9 mF cm -2 , significantly better than Ni3S2 / NF (2.7mF cm -2) and Co3S4 / NF (4.7 mF cm -2 ), indicating that the electrocatalytic composite material Co3S4 / Ni3S2 / NF has the best electrochemical properties.

[0099] In summary, the embodiment of the present invention synthesizes a nano-sheet ZIF-67 precursor by in-situ growth on a nickel foam skeleton, and the structure of the three-dimensional cross-cross nanosheet is more stable, which avoids a large number of problems such as shedding and dissolution of the electrocatalytic composite material during the reaction, so that the stability of the electrocatalytic composite material is significantly improved. Moreover, the nano-sheet structure increases the contact area between the electrocatalytic composite material and the solution, greatly improves the exposure rate of the active site, and significantly improves the electrocatalytic performance of the electrocatalytic composite material. Then, carbonization is carried out in a N2 atmosphere, and the Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material is finally prepared by a hydrothermal method. The structure, composition, morphology, etc. of the electrocatalytic composite material are systematically characterized by characterization methods such as XRD, SEM, TEM, XPS, and UPS. The OER and UOR performance of the Co3S4 / Ni3S2 / NF heterojunction electrocatalytic composite material are studied by LSV curve, Tafel slope, it test, and Faraday efficiency test. The results show that Co3S4 / Ni3S2 / NF is an electrocatalytic composite material with excellent OER and UOR activity. In the OER reaction in 1.0 M KOH, the current density was 10 mA cm -2 When the working potential is only 200 mV, the current density of the Co3S4 / Ni3S2 / NF electrocatalytic composite material in the UOR reaction of 1.0 M KOH / 0.5 M urea is 100 mA cm -2 Its operating voltage is only 1.36V. -2 In the stability test under , the Co3S4 / Ni3S2 / NF electrocatalytic composite material also showed excellent long-term stability and could work stably for more than 100 hours. Therefore, the Co3S4 / Ni3S2 / NF electrocatalytic composite material exhibits excellent electrochemical catalytic performance and stability.

[0100] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. Application of a foamed nickel self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material in electrocatalytic anode oxygen evolution reaction and urea oxidation reaction, characterized in that: The nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material is prepared by the following steps: S1, dissolving a cobalt salt and 2-methylimidazole in water, mixing and stirring to obtain a mixed solution, wherein the molar ratio of the cobalt salt to the 2-methylimidazole is 1:4.9 to 1:5.1; S2, ultrasonically cleaning the nickel foam substrate, immersing the cleaned nickel foam substrate in the mixed solution and reacting at 25-35° C. for 11.5-12.5 h to obtain a zeolite imidazolate framework material with nickel foam as a carrier, which is recorded as ZIF-67 / NF; S3, calcining the ZIF-67 / NF in an inert atmosphere to obtain a metal organic framework material, wherein the heating rate of the calcination is 0.98-1.02° C. / min, the calcination temperature is 590-610° C., and the calcination time is 1.45-1.55 h; S4. Add the metal organic framework material to a thiourea solution with a concentration of 0.3-0.35 mol / L, and carry out a hydrothermal reaction at 155-165°C for 8-8.5 hours to obtain the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material, recorded as Co3S4 / Ni3S2 / NF.

2. The use of the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material according to claim 1 in electrocatalytic anode oxygen evolution reaction and urea oxidation reaction, characterized in that: In step S1, the cobalt salt is one of cobalt nitrate, cobalt sulfate and cobalt chloride.

3. The use of the nickel foam self-supporting cobalt-nickel bimetallic sulfide heterojunction electrocatalytic composite material according to claim 1 in electrocatalytic anode oxygen evolution reaction and urea oxidation reaction, characterized in that: In step S2, the ultrasonic cleaning is performed on the nickel foam substrate in a hydrochloric acid solution and ethanol in sequence, wherein the concentration of the hydrochloric acid solution is 2.5-3.5 mol / L; and the ultrasonic cleaning time is 20-30 min.

Citation Information

Patent Citations

  • Preparation method of Co4S3 / Ni3S2 / Ni (OH) 2 three-phase heterojunction catalyst and application of Co4S3 / Ni3S2 / Ni (OH) 2 three-phase heterojunction catalyst in hydrogen production

    CN118480812A